(untitled) (Journal of Advanced Research in Social Sciences, 2021)
Gender continues to affect how urban spaces are perceived and experienced. Girls and women continue to experience sexual harassment, feel unsafe and conditioned as they live and move in urban environments. Reinforcing the concept "Right to the City" of Henri Lefebvre (1991) and David Harvey (2008), this paper aims to explore the need to promote critical spatial thinking to demystify gender stereotypes, leading to the exercise of active citizenship, able to participate and contribute to the (re)design of an inclusive city. People are social products whose values and beliefs are shaped by society, often perpetuating social practices and norms that promote gender inequalities. It is crucial to enable and encourage critical spatial thinking about women’s environment to understand and recognise existing limitations and constraints. The desire for change begins with awareness of the situation in which we live. Several authors refer to critical thinking as fundamental to the empowerment process, pointing out that by exercising critical reflection on the situation, women challenge gender inequality. The exercise of critical spatial thinking also highlights the need for new communication processes that recognise and enhance the importance of showing and share individual perspectives in the use of urban spaces. It will enrich a more active collective voice, increase civic participation necessary to build safer and gender-equal spaces in urban life.